Factors of turnover intention among employees in financial industry in Klang Valley - Rozaimi, Muhammad Ameerul Hisyam (2020)
A country would be nothing without employers whom to create the job opportunity in a bid of to increase the economics of a country. Employers require the people whom can be considered as an asset for the organization ensuring the work flow of the organization can be run as planned. Employees in the company also are considered as the backbone of the employers that can develop the organization to be operate seamlessly. However, in this era of globalization, employee turnover has become a phenomenal issue which elevated tremendously due to many factors. Turnover in occupational context can be defined as the movement of the employee from one organization to another organization within a particular intention (Abelson, 1993). This common phenomenal is encountered by financial industry in Malaysia since nineties (Inagami, 1998). It is because financial industry in Malaysia is one of essential sectors that lead to the economic development where high demand existing in the market. It has been widely investigated by many researchers and consider as a natural organizational phenomenon that never come to an end. This continuous matter will affect the human resource department in every company particularly the practices of recruitment and selection, training and development and compensation. In consequences, employee’s turnover may lead to insufficient employees and this may drag to another load of burden when other employees need to cover up the responsibility of the prior person who leaves the company (Harper, 2016). Due to that, job stress and dissatisfaction among employees will elevate when they have to bear a ton of workloads that made by other employees.